p-Aminobenzoic acid (pABA) sensitization of LaF3:Tb3+ nanoparticles and its applications in the detection of explosive materials - Ghosh, Debasish; Luwang, Meitram Niraj (RSC Advances, 2015)
This work reports the utilization of water dispersible terbium (Tb3+) doped spherical LaF3 nanoparticles (similar to 5 nm) surface functionalised with p-aminobenzoic acid (pABA) for the detection of aromatic nitro explosives. The functionalised nanoparticles show remarkable sensitivity to a number of highly electron deficient aromatic nitro compounds like picric acid (PA), 2,4,6-trinitrotoluene (TNT), 2,4-dinitrotoluene (2,4-DNT), 2,4-dinitrophenol (2,4-DNP) etc. All of these nitro compounds can be detected easily at ppm level using this luminescence quenching technique whereas in the case of TNT it can detect concentrations as low as 50 ppb. This novel approach of utilising the Tb3+ doped NPs sensitised by pABA has potential application in the detection of explosive materials.